(untitled) (Al-Academy, 2016)
Construction is the opening of the important pillars of the construction of the film as a whole for this, we find that the first of any narrative of my film begin at the borders of this construction is the window that we look through the contents tale and puzzle narrative is of significance that degrade traveler when reservoirs expression later in reasoning and find justifications ills that came by those initiation, this initiation may be the window that lead us to the core, understanding the story through signals received to the recipient to sail because of the paths of pickling what is which is encoded, but this initiation may serve as keys that understanding the be puppies and signals that beset and surrounded to what He holds inevitably. This research focuses on the start-up at the borders of the initiation of the narrative Film if the pattern of this research and the types of essences and functions of narrative and story modes of processors positions across initiation those that are the most important element of excitement and acceptance, as is the case with the poem that read eloquent from its inception